New issues in mediating the Israel-Palestine deadlock - Steiner, Barry H. (Barry Howard), 1942- (Brill Nijhoff, 2018)
The essays in this book, originally published in a special issue of the journal International Negotiation (vol. 23.1, 2018), are intended to enhance America's ability to mediate Israel-Palestine conflict. Every American president for the last thirty years, down to Donald Trump, has chosen to engage in this effort. To help understand and evaluate these efforts, and to focus upon the more promising mediation directions, these essays analyze mediation options in detail. I. William Zartman accentuates special challenges of third party mediation. Amira Schiff critiques John Kerry's mediation effort made on behalf of the Obama Administration. Galia Golan outlines mediation requirements in light of past American mediation efforts. Walid Salem suggests a new paradigm centered upon symmetry rather than asymmetry to assist Israel-Palestine peacemaking. And Barry Steiner studies a specific mediation action proposal.